Niveles de colinesterasa sérica y su relación con los factores de riesgo en fumigadores del área agrícola de Monterrey Azucarera Lojana en la ciudad de Catamayo - Juárez Quezada, Leonardo Alexander (2015)
Cholinesterase is an enzyme that is found in the liver, pancreas, heart, in the white substance of the brain and in plasma; it is consider an indicative of a possible intoxication by organophosphorus pesticides, which inactivate it, as a result this enzyme serves as an indicator of exposition and toxicity to these components. The organophosphates components have as a pharmacologic characteristic to inhibit the enzymes with esteric activity, specifically the acetylcholinesterase in the nerve endings, which generates an accumulation of acetylcholine and, as a consequence, it is altered the functioning of the nerve impulse. It is therefore that the present investigation is focused to determine the levels of serum cholinesterase and to relate them with risk factors in fumigators of the agricultural area of Monterrey Azucarera Lojana, in the city of Catamayo. This is a descriptive and cross-sectional work. It has been analyzed the samples of 53 male fumigators, in the ages between 20 to 60 years; having as a result that 73.6% showed normal values of cholinesterase, while the 26.4% had lower levels of it; these values are related to the inhibitors components of the serum cholinesterase enzyme present in pesticide and to the different risk factors; such as the inadequate use of the protective measures, the poor condition of the fumigation equipment and for consuming food in the work place, which provokes that there exist acute as well as chronical intoxications, which if not diagnosed on time, could bring serious consequences to the health state such as: altering in the functioning of the nerve impulse, drowsiness, delirium, hallucinations, aggressiveness, and even death. Keywords: Cholinesterase, organophosphates, fumigators, enzyme.